Rosmarinic acid suppresses Alzheimer’s disease development by reducing amyloid β aggregation by increasing monoamine secretion - Hase, Tomoki (Sci Rep, 2019)
A new mechanism is revealed by which a polyphenol, rosmarinic acid (RA), suppresses amyloid β (Aβ) accumulation in mice. Here we examined the brains of mice (Alzheimer’s disease model) using DNA microarray analysis and revealed that the dopamine (DA)-signaling pathway was enhanced in the group fed RA versus controls. In the cerebral cortex, the levels of monoamines, such as norepinephrine, 3,4-dihydroxyphenylacetic acid, DA, and levodopa, increased after RA feeding. The expression of DA-degrading enzymes, such as monoamine oxidase B (Maob), was significantly downregulated in the substantia nigra and ventral tegmental area, both DA synthesis regions. Following in vitro studies showing that monoamines inhibited Aβ aggregation, this in vivo study, in which RA intake increased concentration of monoamine by reducing Maob gene expression, builds on that knowledge by demonstrating that monoamines suppress Aβ aggregation. In conclusion, RA-initiated monoamine increase in the brain may beneficially act against AD.